Enhancing Hard Surface Modeling with Blender: A Comparative Review of Its Applications in Education, Industry, and Gaming in Pakistan and China - Ayaz Muhammad Hanif; Zohra Saleem; Abdul Waheed Khan; Fu Kaili (Journal of Design and Textiles, 2025)
This research explores the transformative influence of Blender, an open-source software, on hard surface modeling across educational, industrial, and gaming sectors in Pakistan and China. Despite the growing global adoption of Blender, there is a lack of comparative studies analyzing its impact in diverse socio-economic and technological landscapes. This study addresses this gap by exploring how Blender’s integration differs in these two regions, emphasizing skill development, cost-effectiveness, and innovation. Using a mixed-methods approach involving surveys, case studies, and literature reviews, the findings reveal how Blender is integrated into curricula, supports affordable industrial applications, and enables the creation of gaming assets. Pakistan focuses on cost-effective grassroots initiatives, whereas China relies on structured, government-endorsed strategies for large-scale industrial applications. Educational institutions in both countries show a significant uptake of Blender, with China achieving superior results due to its advanced infrastructure. In the gaming sector, Blender allows Pakistani developers to create globally recognized indie games and empowers Chinese companies to produce AAA titles. Key challenges include limited infrastructure in Pakistan and standardization issues in China. The paper concludes with recommendations for integrating AI, fostering cross-border collaboration, and developing tailored training programs. The study recommends Pakistan emulate China's model with state support for long-term development. Future studies could explore Blender’s role in emerging economies and its future for works designed in the metaverse. The study underscores Blender as an important, affordable tool that balances price with requirements in the field, and securing its position in the global virtual environment.